2020
DOI: 10.3390/nu12061861
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Improve Health Communication: Can Health Professionals Be Heroes?

Abstract: Communicating evidence-based nutrition messages to the public is challenging and is often in conflict with popular opinions, particularly from social media influencers (SMIs). In order to increase engagement with nutrition professionals (NPs) on social media, we aimed to explore young adults’ perceptions of the authenticity and trustworthiness of SMIs and NPs Instagram posts. A cross-sectional questionnaire was administered to students (n = 149) from an Australian University. Participants viewed a real-life In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 64 publications
(121 reference statements)
0
23
0
2
Order By: Relevance
“…Most studies have examined Facebook and Twitter, whereas trustworthiness on Instagram and YouTube has been studied less frequently [26,27]. The research shows that credibility is judged differently on the 2 platforms; for example, personalized language was an effective way to increase credibility on Facebook, but depersonalized tweets were more credible on Twitter [27,28].…”
Section: How Young People Use Social Media For Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have examined Facebook and Twitter, whereas trustworthiness on Instagram and YouTube has been studied less frequently [26,27]. The research shows that credibility is judged differently on the 2 platforms; for example, personalized language was an effective way to increase credibility on Facebook, but depersonalized tweets were more credible on Twitter [27,28].…”
Section: How Young People Use Social Media For Healthmentioning
confidence: 99%
“…A recent review found that the credibility of social media health information is affected by language used, perceived expertise, and bandwagon cues, such as the number of likes a post receives [26]. Most studies have examined Facebook and Twitter, whereas trustworthiness on Instagram and YouTube has been studied less frequently [26,27]. The research shows that credibility is judged differently on the 2 platforms; for example, personalized language was an effective way to increase credibility on Facebook, but depersonalized tweets were more credible on Twitter [27,28].…”
Section: How Young People Use Social Media For Healthmentioning
confidence: 99%
“…Specifically, there is a great degree of heterogeneity among young adults with varying levels of engagement (e.g., super sharers, sharers, posters, lurkers and no engagement) [ 60 ]. It is suggested that complex interventions need to account for young adults’ variation in social media use and use an array of techniques, such as social support [ 60 ], gamification [ 61 ] and different messaging [ 62 , 63 ] to enhance engagement. In addition, it is important to consider user feelings around certain foods and how social media content can impact on this.…”
Section: Discussionmentioning
confidence: 99%
“…Gabarron et al ( 21 ) revealed that health education on social media, such as Facebook and Instagram should consider videos and emoji in their posts to increase user engagement. Jenkins et al ( 22 ) found that nutrition professionals should convey positive emotions and success to enhance the trustworthiness of their posts. However, there remains a lack of quantitative analysis and empirical research on how to accurately parse out the health needs of users from massive amounts of health information.…”
Section: Introductionmentioning
confidence: 99%